9(3n+3)=7(7n+7)+7

Simple and best practice solution for 9(3n+3)=7(7n+7)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(3n+3)=7(7n+7)+7 equation:


Simplifying
9(3n + 3) = 7(7n + 7) + 7

Reorder the terms:
9(3 + 3n) = 7(7n + 7) + 7
(3 * 9 + 3n * 9) = 7(7n + 7) + 7
(27 + 27n) = 7(7n + 7) + 7

Reorder the terms:
27 + 27n = 7(7 + 7n) + 7
27 + 27n = (7 * 7 + 7n * 7) + 7
27 + 27n = (49 + 49n) + 7

Reorder the terms:
27 + 27n = 49 + 7 + 49n

Combine like terms: 49 + 7 = 56
27 + 27n = 56 + 49n

Solving
27 + 27n = 56 + 49n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-49n' to each side of the equation.
27 + 27n + -49n = 56 + 49n + -49n

Combine like terms: 27n + -49n = -22n
27 + -22n = 56 + 49n + -49n

Combine like terms: 49n + -49n = 0
27 + -22n = 56 + 0
27 + -22n = 56

Add '-27' to each side of the equation.
27 + -27 + -22n = 56 + -27

Combine like terms: 27 + -27 = 0
0 + -22n = 56 + -27
-22n = 56 + -27

Combine like terms: 56 + -27 = 29
-22n = 29

Divide each side by '-22'.
n = -1.318181818

Simplifying
n = -1.318181818

See similar equations:

| 2(x-4)=-12(3x+1) | | 2(0.5-y)=4.6 | | 7x-5(3x-7)=11 | | x^2=3n | | (7x-16)+(x+8)+(4x)=180 | | 13x+2y=10 | | 12(3)(-2)= | | 8-2h=58 | | 5y+2x=60 | | 3(x+6)+3=3+5(x-4) | | 4p^2+12p+3=0 | | 8e+4-(3+9e)= | | 6.2a+10=72 | | 2m+4m=m | | (12x^2)-8x=0 | | 6x(-12)= | | 5(x+16)=x-8 | | 6(x-1)=16 | | 2x+5x-6=9x-8 | | 2x+4(x-8)=-52 | | 143-4x=5x-136 | | 9.06x+63.42=126.84 | | ln(7x+20)=ln(4x-4) | | (x)=1/2(X) | | 9.06+63.42=126.84 | | 2/5*2/5= | | 7x=2+15y | | 9/10x-3/5=9 | | 10=24+18x | | 4x-12=-12-(-4x) | | (x)=3x-12 | | y-6=31 |

Equations solver categories